2020
DOI: 10.1155/2020/3809734
|View full text |Cite
|
Sign up to set email alerts
|

A Mixed Integer Linear Programming Model for Rolling Stock Deadhead Routing before the Operation Period in an Urban Rail Transit Line

Abstract: In an urban rail transit line, train services are performed by the rolling stocks that are initially stored at depots. Before the start of the operation period, rolling stocks consecutively leave the depots and run without passengers (deadhead routing) to the origin station of their corresponding first departure train service in an operation day (first train service) using either direct or indirect routes. This paper investigates the rolling stock deadhead routing problem in an urban transit line with multiple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…First, instead of ensuring the arrival and departure safety headway between two different trains running in the same direction, the explicit consideration of train entrance and exit route conflicts can increase the station throughput capacity and reduce the train delays [10,20]. Second, the MILP model and the heuristic algorithm GSAHA proposed in this paper can be further developed to consider different station types, such as the terminal station where trains need to perform the turnaround movement that makes the train platforming problem more complicated [42,43]. ird, the train movements at the stations can be viewed as a set of space-time paths, and thus more efficient dual decomposition methods could be developed accordingly [7,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…First, instead of ensuring the arrival and departure safety headway between two different trains running in the same direction, the explicit consideration of train entrance and exit route conflicts can increase the station throughput capacity and reduce the train delays [10,20]. Second, the MILP model and the heuristic algorithm GSAHA proposed in this paper can be further developed to consider different station types, such as the terminal station where trains need to perform the turnaround movement that makes the train platforming problem more complicated [42,43]. ird, the train movements at the stations can be viewed as a set of space-time paths, and thus more efficient dual decomposition methods could be developed accordingly [7,44,45].…”
Section: Discussionmentioning
confidence: 99%
“…Method extensions and practical applications were also discussed. In addition, evaluation work can be further combined with other transportation organization or disruption management research to formulate collaborative optimization strategies, such as robust train timetabling [57], train platforming [58], rolling stock scheduling [59], and energy saving [60]. e method of parameter estimation needs to be improved.…”
Section: Discussionmentioning
confidence: 99%
“…The study by Borndörfer, et al [51] indicates that spacing allocation to perform maintenance involving maintenance pit (infrastructure capacity) is included in constraint for rolling stock practitioner to perform appropriate maintenance activity. According to the research conducted by Zhong, et al [52] and Giacco, et al [53], the location of the fleet part also contributes to the maintenance cost. These studies have shown that, TOC with mixed fleets has to find tune strategic location and size of the fleet park within their network.…”
Section: Facilities Related Costmentioning
confidence: 99%